1998
DOI: 10.1023/a:1022620217886
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Behavior rating scales are commonly used in the assessment of attention deficit-hyperactivity disorder (ADHD). However, there is little information available concerning the extent to which scales are valid with culturally different students. This study explored the use of the ADHD-IV Rating Scale School Version with male Caucasian (CA) and African American (AA) students from ages 5 to 18 years. Teachers rated AA students higher on all symptoms across all age groups. LISREL analysis indicated that scale does no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(36 citation statements)
references
References 12 publications
1
35
0
Order By: Relevance
“…Thus, the findings can be taken to suggest strong support for measurement invariance across adolescent male and female self-ratings of the ADHD symptoms in the DBRS-SR. Although the findings in the current study are consistent with existing gender invariance data for the ADHD symptoms (Burns et al, 2006;Gomez, 2007;Gomez, in press;Reid et al, 1998), they extend existing data. Unlike previous studies, which examined parent and teacher ratings, the current study examined adolescent self-ratings, and also recoded binary scores.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Thus, the findings can be taken to suggest strong support for measurement invariance across adolescent male and female self-ratings of the ADHD symptoms in the DBRS-SR. Although the findings in the current study are consistent with existing gender invariance data for the ADHD symptoms (Burns et al, 2006;Gomez, 2007;Gomez, in press;Reid et al, 1998), they extend existing data. Unlike previous studies, which examined parent and teacher ratings, the current study examined adolescent self-ratings, and also recoded binary scores.…”
Section: Discussionsupporting
confidence: 89%
“…For U.S. children, Reid et al (1998) found support for gender invariance for configural and metric invariance for the original four ordered response-category scores for teacher ratings of children on the ARS-IV, whereas for Malaysian children, Burns et al (2006) reported similar findings, and also for scalar invariance, error variances invariance, and invariance for construct variances, covariance, and mean scores for the original four ordered response-category scores for parent ratings of the DBRS. The Burns et al study also found this for U.S. parent ratings of children for the Child and Adolescent Disruptive Behavior Inventory-2.3 (CADBI; Burns, Taylor, & Rusby, 2001).…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…On one hand, the factorial structure of ADHD, like the general structure of common psychopathology (or at least, of common childhood problems) appears to be to a large extent universal across a wide range of cultural and racial groups (Bauermeister, Canino, Planczyk, & Rohde, 2010). Likewise, measurement and structural invariance were supported when comparing Malaysian parent ratings to those of Australian (Gomez, 2009) and American parents (Burns, Walsh, Gomez, & Hafetz, 2006), although not when comparing African American and Euro-American youth as Reid et al (1998) reported. Moreover, recent data (Frazier et al, 2011) suggest that African American youth are now about as likely as Caucasian American youth to be diagnosed and treated for ADHD, unlike data just a few years earlier.…”
Section: Cultural and Historical Contexts Of Developmentmentioning
confidence: 95%
“…However, a number of studies also indicate that African American children are rated as displaying more behavioral problems on teacher-report scales (e.g., Epstein et al, 2005; Piggott & Cowen, 2000; Reid et al, 1998). Moreover, because many minority families live at or near the poverty level, the direct and indirect effects of SES on child behavior may impact them disproportionately (Koblinksy, Kuvalanka, & Randolph, 2006).…”
Section: Relation To Ses and Ethnicitymentioning
confidence: 99%